Flipping the Classroom and Students’ Performance in Physics - Akanbi, Abdulrasaq Oladimeji; Eben, Olasunkanmi Tayo; Yusuf, Aishat Abdulqadir (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The study examined flipping the classroom and students' performance in physics. The study adopted the quasi-experimental design. The population for this study was all senior school two (SS II) students offering Physics. Three research instruments were used for data gathering and were analyzed with the t-test, ANOVA, and ANCOVA to test all the formulated hypotheses at the 0.05 alpha level. The results showed that there was no significant difference in the performance of students taught Simple Harmonic Motion using flipped classroom instructional strategy and those taught with the conventional teaching method, no significant difference in the performance of male and female students when taught using Flipped Classroom Instructional Strategy, no significant difference between low and medium scorers and there is a statistically significant two–way interaction effect between gender and score level when students are taught using flipped classroom instructional strategy. It was recommended, among others, that flipped classrooms be implemented in teaching other topics in physics.